L'alluvione generale del 4 novembre 1966 - Gorfer, A (Natura Alpina, 1967)
alluvioni e frane recenti
Keywords: geomorfologia, fluviale, versante, Attuale, Trentino, Trento, Avisio, Valsugana, Primiero, Valle del Cismon, Val Rendena, Olocene, Subatlantico